16 DIETARY PECTIN ALLEVIATES CHRONIC COLITIS BY PROMOTING NLRC4-MEDIATED IL-1RA PRODUCTION. (7th February 2019) - Singh, Vishal; Yeoh, Beng San; Golonka, Rachel M; Vijay-Kumar, Matam
Abstract: Dietary soluble fibers have many beneficial effects on gastrointestinal (GI) health; however, the mechanisms by which these fibers attenuate intestinal inflammation during colitis remains elusive. We propose that fiber-derived gut metabolites diminish intestinal inflammation via regulating NOD-like-receptor C4 (NLRC4) inflammasome signaling in the GI tract. To demonstrate this, C57BL/6 mice were fed either dietary cellulose (insoluble fiber) or pectin (soluble fiber) and administered three weekly injections of IL-10 receptor neutralizing antibody (α-IL-10R) to induce chronic colitis. Mice were euthanized two weeks after the last dose, and colitis development was examined by serological, biochemical, histological and immunological parameters. Wild-type (WT) mice receiving dietary cellulose along with α-IL-10R exhibited robust colitis—as characterized by splenomegaly, colomegaly, elevated systemic [serum amyloid A (SAA), lipocalin 2 (Lcn2) and keratinocyte-derived chemokine (KC)] and colonic [Lcn2 and interleukin (IL)-1β] pro-inflammatory cytokines, and colon histology score—when compared to control mice. Compared to cellulose, dietary pectin ameliorated colitis development, supporting the notion that dietary soluble fibers are beneficial for gut health. Similar results were observed in Toll-like receptor 5 knockout mice, which are prone to develop microbiota-dependent spontaneous colitis. Remarkably, we noted that pectin-fed mice had heightened expression of NLRC4, primarily in colonic epithelial crypts, as evident via immunohistochemical staining. Alongside with increased NLRC4, there was reduced expression of NLRP3, albeit with high variability, in pectin-fed mice. More importantly, the colonic level of IL-1 receptor antagonist (IL-1Ra; aka anakinra), whose expression is partly regulated via NLRC4, was elevated in mice fed with pectin. The lack of pectin-mediated protective effects in α-IL-10R-treated NLRC4-deficient and IL-1Ra-deficient mice affirmed that the NLRC4-IL-1Ra axis executes the beneficial effects of pectin during gut inflammation. Considering that IL-1Ra restrains the pro-inflammatory activity of IL-1β, this study suggests that dietary-soluble fiber derived metabolites promote NLRC4 signaling, which augments IL-1Ra and thus limits IL-1β mediated colonic inflammation. Collectively, our study demonstrates that NLRC4 is indispensable for dietary pectin-mediated beneficial effects on gut health.